Можливість розвитку критичного мислення молодших школярів під час навчання розв’язуванню задач - Чосік, Леся; Chosik, L. (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті визначено сутність критичного мислення, подано його особливості, проаналізовано можливості розвитку критичного мислення молодших школярів у процесі навчання математики. Курс математики в початкових класах містить великі можливості для використання різних навичок і прийомів мислення. Систематична орієнтація учнів на їх застосування допомогла б їм оволодіти цими навичками і прийомами і самостійно використовувати їх в навчальній діяльності. Вчителеві потрібно використовувати всі можливості на уроці, де можна було б працювати в даному напрямі. У початковому курсі математики займають особливе місце задачі. Вони відіграють значну роль у розвитку мислення, вихованні навичок розумової праці. Більшість якостей критичного мислення можна формувати у процесі навчання розв’язуванню задач. Проаналізовано розв’язування задач та складові навчання розв’язування задач, які сприяють розвитку критичного мислення. In the article the essence of critical thinking, given its features, analysis capabilities critical thinking younger pupils in learning mathematics. The mathematics in primary school provides a great opportunity to use different skills and ways of thinking. Systematic focus pupils on their use would help them acquire these skills and techniques and use them on their own educational activities. Teacher must use all the features of the classroom, where they could work in this direction. In the initial course of mathematics have a special place problem. They play a significant role in the development of thinking skills education of knowledge workers. Most critical thinking skills can be molded in the learning process of solving problems. Analyzed solving and learning components solving problems that promote critical thinking. Training pupils evaluating the advantages and disadvantages of each method of solving is of great importance for the development of the ability to appropriate methods of variation, flexibility of thinking. Equally important in shaping the thinking skills are also different types of creative work on tasks: Re-solving, change elements of (numerical data, questions, story, several links, the gradual complication of conditions) solve problems in different ways, expressions by compiling tasks, drafting tasks (the specified action on numerical data, expression or solution, the desired values or change the relationship between the values of a certain type, inverse problems).
The ability of critical thinking while pupils solving
Keywords: критичне мислення; молодші школярі; початковий курс математики; розв’язування задач; critical thinking; younger pupils; the initial course of mathematics; solving tasks